Factors Influencing the Practice of Fertility Control among Married Women in Emure Local Government Area, Ekiti State, Nigeria (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2015)
The study investigated the factors influencing the practice of fertility controlamong married women in Emure Local Government Area of Ekiti State of Nigeria.Descriptive research design of the survey type was used to conduct the study among 220women in Emure Local Government. Simple random and stratified sampling techniqueswere used in selecting the respondents. A pretested, close-ended questionnaire was adaptedfrom related studies. The reliability of the instrument was determined with Cronbach alphawhere a coefficient of 0.68 was obtained. The research questions were answereddescriptively while the formulated hypotheses were tested at 0.05 level of significanceusing t-test and Pearson Product Moment Correlation. The results revealed that aconsiderable number of the respondents practised fertility control while injectables and oralpills topped the preferred methods of fertility control. The fear of adverse effects andopposition to fertility control by husbands were the major identified reasons influencing thepractice of fertility control. Also, there was no significant difference between respondentsin rural and urban location on factors influencing fertility control but a negative significantrelationship was found between practice and factors influencing the adoption of fertilitycontrol. Based on the findings, it was recommended that health workers should sensitize thepopulace on the benefits of a planned family. The populace should be informed on thevarious methods of fertility control and routine sensitization should be done through themass media.
Keywords: Fertility control, Married women, Contraceptive, Influencing factors, Practice